Komparasi Performasi Node Router Tengah dan Node Router Tepi pada Jaringan Manet menggunakan Protokol Olsr dan Batman - Novan Ferdiansyah; Nugroho Suharto (Politeknik Negeri Malang, 2019)
The development of wireless technology has created a new network, namely the MANET network. In a MANET network, a node can be a router or an end user because in a MANET network the node is flexible. MANET networks have proactive OLSR and BATMAN protocols. When a node becomes a router, many other nodes will pass it. This research was conducted to determine the formation of the router node in the middle, namely the router that is passed by a lot of communication and the edge, that is, the router that has little communication through the network using parameters of CPU usage, RAM usage, and processing delay. From the test results, the CPU value on OLSR and BATMAN for the middle router node is 0.3 and for the edge router it is 0.2 when communicating, when there is no communication the CPU value on OLSR is still 0.3 while in BATMAN the BATMAN value drops to 0.2. For memory used in both protocols get 0.0 because the router only forwards packets without needing to process the packet. For processing delay in the two protocols, the value varies because packet delivery has an uncertain delivery interval between packets. In BATMAN protocol, CPU usage is better than OLSR because if there is no data communication, the CPU value from BATMAN goes down and on OLSR there is no fixed CPU value communication.